(3egeI djhf QhT aj GdLRGFQ h GdeZQH (B1832-1847 /s - (3efGUQjI,jhSa s ((3GdLRGFQ (B:s (3GdeDSSIGdhWfjI ddcJGH ,s, 1990)
(3gPG GdcJGH jJfGhd ehVhYG NWjQG hgh cTa GdTNUjGJ GdONjdI YdjfG h GdJj JgOO MVGQJfG hJfNQ LSOgG ef GdOGNd (B.(3hef gPg GdTNUjGJ(B,(3djhf QhT GdPj NGOYfG jGSe GdGSdGe eKdeG jNOYfG GdcKjQhf Gdjhe (B,(3hjJQHUhf HfG GdOhGFQ (B.(3hdcj JYQa Gdbdjd Yf gPg GdTNUjI jLH bQCI gPG GdcJGH HYfGjI cHjQI hCNO GdYHQI h GdOQhS ef GdeGVj dHfGA GdOhGFQ (B.(3h dcj JYQa Gdbdjd Yf GdTNUjI jLH bQCI gPG GdcJGH HYfGjI cHjQI h CNP GdYHQI hGdOQhS ef GdeGVj dHfGA GdMGVQ h GdeSJbHd (B.s
Keywords: (3GdLRGFQ s; (3QhT s; (3djhfs; (3egeIs